Primary Cervical Extraosseous Ewing’s Sarcoma Originated from the Sternocleidomastoid Muscle: A Case Report and Review of the Literature - Sasa Jakovljevic; Nenad Arsovic; Zoran Dudvarski; Nemanja Radivojevic; Katarina Jovanovic; Neda Mladenovic; Snezana Babac (Case Reports in Otolaryngology)
Extraosseous Ewing’s sarcoma is extremely rare in the soft tissues of the neck, especially in the sternocleidomastoid muscle. It usually manifests clinically as a rapidly growing mass that shows great potential for local spread. The aim of this paper is to present a rare case of еxtraosseous Ewing’s sarcoma in the sternocleidomastoid muscle. To the best of our knowledge, this is the first case of extraskeletal Ewing’s sarcoma at this location. The patient was admitted to our clinic because of a neck tumefaction. The computerized tomography finding showed a tumor mass, most of which was in the V region of the neck, measuring 40 × 27 × 35 mm. Pathohistological and immunohistochemical findings showed that it was Ewing’s sarcoma. Unfortunately, the patient passed away nine months after the initial diagnosis. Extraosseous Ewing sarcoma is a rare, fast-growing malignant tumor manifesting histomorphological similarities to bone Ewing’s sarcoma. Most reports state that extraosseous Ewing sarcoma has a worse prognosis than skeletal. Extraosseous Ewing sarcoma should be borne in mind in the differential diagnosis of soft tissue tumors of the neck.